Change of angiogenesis in the nodular form of benign mammary dysplasia during treatment with alkaloids, flavonoids and glycosides - Liliana V. Pokul'; Nina A. Chugunova; Marina G. Lebedeva; Ivan M. Sorokivskii; Anna P. Uriupina; Elena A. Solov'eva; Anna M. Utkina (IP Berlin A.V., 2022)
Introduction. The formation of new blood vessels is called angiogenesis. As the tumor grows, the oxygen and nutrient requirements of the abnormal cells continuously increase, and new blood vessels are formed. These processes are disrupted by angiogenesis inhibitors. Therefore, it is warranted to investigate ways to enhance the capabilities of angiogenesis inhibitors alkaloids, flavonoids, and glycosides. Aim. To justify the extension of clinical use of alkaloids, flavonoids and glycosides (Conium maculatum and Hydrastis canadensis, Thuja occidentalis), being a part of the complex medical product Mastopol, taking into account the obtained data on the angiogenic balance in the nodular form of benign mammary dysplasia (BMD). Materials and methods. The study included 69 volunteers divided into two groups: Group 1 included 27 patients with medical history of surgery for nodular BMD who received antiproliferative preoperative therapy with Mastopol for 12 weeks. Group 2 (comparison group), n=42, also included patients with medical history of surgery for nodular BMD but without preoperative therapy with the herbal medicine Mastopol. We studied angiogenesis markers (VEGF-A [vascular endothelial growth factor] and pVEGF-1) and immunohistochemical marker CD34 (cluster of differentiation CD). Results. We found a significantly higher (p0.001) rate of CD34 detection on medium and small caliber vessels in the comparison group, i.e., in the patients who were not treated preoperatively with alkaloids, flavonoids, and glycosides (Mastopol), while blood supply to the nodules by the medium and small vessels was 1.4 and 1.8 times lower in the Group 1, respectively. Analysis of VEGF expression shows an increase of angiogenic promoters VEGF-A and pVEGF-1 in serum before treatment with biologically active herbal components of Mastopol in both groups. There were no statistically significant differences in vascular markers. However, a statistically significant decrease in VEGF-A and pVEGF-1 (p0.001) was noted in Group 1 after Mastopol therapy. Note the presence of a moderate direct correlation (rs=0.49) of CD34 expression with VEGF-A expression in Group 1 and rs=0.41 in Group 2, which indicated a direct relationship between angiogenesis and proangiogenic factors. Conclusion. In addition to the proven antiproliferative, anti-inflammatory, cytokine stabilizing, analgesic, and anti-edema properties of Mastopol, the study also showed the antiangiogenic effect of the herbal drug components. Considering the decreased vascular growth in fibroadenomas during Mastopol treatment, the indications for its use in patients with fibroadenomas before the surgery can be extended. Specific immunological test to measure VEGF can be proposed as a noninvasive screening method to evaluate the effectiveness of conservative treatment in general clinical practice.